PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN MINAHASA UTARA (The Role of Agricultural Sector in the Economy of North Minahasa Regency) - Sandro Kaemba; Esry O.H. Laoh; Oktavianus Porajouw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of this research is to describe the Role of the Agricultural Sector in the Economy of North Minahasa Regency. Data collection in this research is in the form of secondary data obtained from the Central Statistics Agency of North Sulawesi Province. The calculated variable is the North Sulawesi Province GRDP value from 2010 to 2017 ADHK in 2010, North Minahasa Regency GRDP value from 2010 to 2017 ADHK 2010. The research result showed that the Agriculture Sector still has an important role in the economy of North Minahasa Regency and the Sector Agriculture is one of the basic sectors in North Minahasa Regency, although the contribution of the Agriculture Sector tends to decrease every year.Keywords: Role - Â Agricultular Sector-Economy